2015
DOI: 10.1007/978-3-319-13024-8
|View full text |Cite
|
Sign up to set email alerts
|

Migrating and Settling in a Mobile World

Abstract: This series is the official book series of IMISCOE, the largest network of excellence on migration and diversity in the world. It comprises publications which present empirical and theoretical research on different aspects of international migration. The authors are all specialists, and the publications a rich source of information for researchers and others involved in international migration studies.The series is published under the editorial supervision of the IMISCOE Editorial Committee which includes lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 180 publications
1
12
0
Order By: Relevance
“…While preparation prior to return (Bhugra, 2004; Cassarino, 2004; Gmelch, 1980) plays an important role in reducing the negative psychosocial consequences, it appears that the return of migrants and their children who have tended towards assimilation into the host country’s culture is bound to have psychosocial consequences for the minor returnees. A general lack of identification with the Albanian culture prior to relocation to Albania (Vathi, 2015) is another contrasting feature with previous research (e.g. Ní Laoire et al, 2011 researched children aged 3–18 years old who relocated to Ireland, emphasising the strong sense of being Irish while reporting no psychological consequences).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…While preparation prior to return (Bhugra, 2004; Cassarino, 2004; Gmelch, 1980) plays an important role in reducing the negative psychosocial consequences, it appears that the return of migrants and their children who have tended towards assimilation into the host country’s culture is bound to have psychosocial consequences for the minor returnees. A general lack of identification with the Albanian culture prior to relocation to Albania (Vathi, 2015) is another contrasting feature with previous research (e.g. Ní Laoire et al, 2011 researched children aged 3–18 years old who relocated to Ireland, emphasising the strong sense of being Irish while reporting no psychological consequences).…”
Section: Discussionmentioning
confidence: 77%
“…Such age-specific changes have implications for socialisation; as mentioned above, confrontations with peers are an important phenomenon of the early stage of adaptation of the participants, and as a factor that affects their psychosocial wellbeing. Although the experience of being singled out is not exclusive to the Albanian-origin children (Christou, 2006; Ní Laoire, 2011b), the discrimination that Albanian migrants and their children experienced in the receiving countries (Vathi, 2015) makes their return experience a ‘double racism’ story – ‘racism there, and racism here’, as some participants put it, referring to instances of perceived racism in both Greece and Albania.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following sayings were frequent in their narratives: 'Our children are happy here; they were born here, they have their friends, and they wouldn't like to go anywhere else'. Similarly, Vathi (2015) suggested that children's attachment to the host society, and in particular identification with the locality, hindered parents' return plans.…”
Section: Barrier S To Onward Mig R Ation and The Reconfig Ur Ation Of...mentioning
confidence: 99%
“…Settlement is commonly linked to negotiation of social capital means, such as employment, often surrounded by perceived racism and discrimination, cultural adaptation, and integration factors (Alemi & Stempel, 2018;Nannestad et al, 2013;Renzaho et al, 2011;Vathi, 2015). The differences and subjectivity in the context of their experiences may have an impact on how they ensure that their children have the best possible health outcomes.…”
mentioning
confidence: 99%